A Socio-Economic Survey of Baroda City - Planning Commission (Planning Commission, 1957)
The city of Baroda is situated in 22°, 17', 59" in North Latitude and in 73°, 15', 8" in East Longitude. A small river, Vishwamitra passes in south western direction through the western part of the city. An important junction on the Western Railway, Baroda is 244½ miles north of Bombay and 61½ miles south-east of Ahmedabad. It is 130' above the sea-level. Till lately, the city was the capital of the State of Baroda under the Gaekwads. In 1949, the State was merged in Bombay and since then the city is the head-quarters of Baroda District. The ancient city of Baroda covered only a part of the present city. Probably till the 17th century, the city covered only that portion which now lies within the four gates. Outside the city walls, the country was scattered over with fields, fences, wells and mosques.
Research Programme Committee